Serological Evidence for the Association Between Epstein-Barr Virus Infection and Sjögren’s Syndrome - Xuan, Jingxiu; Ji, Zhiqian; Wang, Bin; Zeng, Xiaoli; Chen, Rongjuan; He, Yan; Rao, Peishi; Wu, Puqi; Shi, Guixiu (Frontiers in Immunology, 2020)
Background: Exposure to Epstein-Barr virus (EBV) infection has been hypothesized to be an important risk factor for multiple rheumatic diseases, but the serological evidence so far for its role in Sjögren's syndrome (SjS) is not clearly established yet. This study aimed to assess the seroepidemiological associations of antibodies to EBV with SjS. Methods: A seroepidemiological study containing 119 patients with SjS and 65 healthy controls was first performed, in which the associations of SjS with 4 commonly studied EBV antibodies including IgM-anti-viral capsid antigen (anti-VCA) antibody, IgG-anti-VCA antibody, IgG-anti-early antigen (anti-EA) antibody and IgG-anti-EBV nuclear antigen 1 (anti-EBNA1) antibody were evaluated. A systematic review and meta-analysis of eligible seroepidemiological studies was also carried out, and data syntheses were performed using random-effect meta-analysis. Results: In the case-control study, the patients with SjS had both a significantly higher prevalence of IgG-anti-EA antibody positivity (31.9% vs 3.1%, P < 0.001) and high titers of IgG-anti-EA antibody (P < 0.001) than healthy controls. The titer of IgG-anti-VCA antibody was significantly increased in the patients with SjS compared with healthy controls (P < 0.001). IgG-anti-EA antibody seropositive patients with SjS had lower levels of both C3 (P = 0.002) and C4 (P = 0.02), and the titer of IgG-anti-EA antibody was inversely related to the levels of both C3 (r = -0.31, P < 0.001) and C4 (r = -0.20, P = 0.03). A total of 14 eligible studies on the serological associations between EBV infection and SjS were finally included into the meta-analysis, which suggested obvious associations of SjS with IgM-anti-VCA antibody (Odds ratio [OR] = 5.77, 95%CI 1.73-19.25, P = 0.004) and IgG-anti-EA antibody (OR = 9.97, 95%CI 4.58-21.67, P < 0.00001). Conclusions: The findings from this study provide strong serological evidence for the association between EBV infection and SjS. SjS has obvious associations with IgM-anti-VCA antibody and IgG-anti-EA antibody. IgG-anti-EA antibody is linked to low levels of C3 and C4 in the patients with SjS, the significance of which needs to be addressed in further studies.